A retrospective cohort study comparing a novel, spherical, resorbable particle against five established embolic agents for uterine fibroid embolisation. Issue 6 (June 2021) - Maclean, D.; Vigneswaran, G.; Bryant, T.; Modi, S.; Hacking, N.
Abstract : AIM: To evaluate the effectiveness of a novel, resorbable, spherical embolic agent compared with other established agents, by studying percentage fibroid infarction (the best indicator of long-term symptom improvement) in patients undergoing uterine fibroid embolisation (UFE). MATERIALS AND METHODS: This retrospective cohort study examined six different embolic agents used for fibroid embolisation, including a new gelatin-based, fully resorbable, spherical agent. The primary effectiveness outcomes were magnetic resonance imaging (MRI)-determined dominant fibroid infarct percentage (DF%) and all fibroid percentage infarct (AF%) at 3 months post-embolisation. MRI-determined uterine artery patency rate was the secondary outcome. Chi-squared test (χ 2 ), relative risk (RR) calculation (primary outcomes), and analysis of variance (ANOVA) (secondary outcome) were the statistical tests employed. RESULTS: One hundred and twenty patients were treated with six embolic agents (20 consecutive patients per group, overall mean age 44.8±6.4, initial uterine volume 570±472 ml, dominant fibroid volume 249±324 ml). Fibroid infarctrates were similar between the cohorts with no significant difference between the new gelatin-based resorbable particle and other embolics in either DF% (χ 2 =3.92, p= 0.56) or AF% (χ 2 =2.83, p= 0.73). Complete DF% RR=1.07 (0.90–1.27) and AF% RR=1.09 (0.85–1.41) suggest non-inferiority of the resorbable particle (d=0.67, p< 0.05). A favourable uterine artery patency rate was demonstrated for the resorbable particle compared with gelatin slurry (82.5% versus 27.5%, p< 0.001 after Bonferroni adjustment). CONCLUSIONS: This new gelatin-based, fully resorbable particle is an effective embolic agent for fibroid embolisation and achieves an infarct rate non-inferior to established embolics. Highlights: This is the first comparative study of this new spherical, resorbable agent. MRI Fibroid infarction is the best indicator of long-term symptomatic improvement. Gel-bead was found to be non-inferior in percentage fibroid infarction. A superior uterine artery patency rate compared with Gelfoam was demonstrated.